Does the common law power to grant cross‐border insolvency assistance apply to an insolvency winding‐up that is voluntary? The reaction to Singularis from Singapore and Hong Kong. Issue 3 (27th November 2019) - Qu, Charles Zhen; Godwin, Andrew
Abstract: In many common law jurisdictions, the common law power of courts to grant assistance in respect of foreign insolvency proceedings exists independently of statute. The nature of the power, however, continues to generate debate. Obiter dicta of the Privy Council suggests that no assistance is available where the foreign proceeding is a voluntary winding‐up. This article evaluates the position by reference to Singapore and Hong Kong decisions and concludes that a refusal to grant assistance in circumstances involving an insolvent voluntary winding‐up is inconsistent with the principle of modified universalism and that a broader recognition test should be adopted.